Quantification of Intracranial Structures Volume in Fetuses Using 3-D Volumetric MRI: Normal Values at 19 to 37 Weeks' Gestation - Ren, Jing-Ya; Zhu, Ming; Wang, Guanghai; Gui, Yiding; Jiang, Fan; Dong, Su-Zhen (Frontiers in Neuroscience, 2022)
OBJECTIVE. The purpose of this study is to establish intracranial structures volume reference in normal fetuses range from 19 to 37 weeks’ gestation (mean 27weeks). MATERIALS AND METHODS. A retrospective analysis of 188 MRI examinations (1.5 T) of fetuses with a normal brain appearance (19–37 gestational weeks) from January 2018 to December 2021 were included in this study. 3-D volumetric parameters from slice-to-volume reconstructed (SVR) images, including total brain volume (TBV), cortical gray matter volume (GMV), subcortical brain tissue volume (SBV), intracranial cavity volume (ICV), lateral ventricles volume (VV), cerebellum volume (CBV), brainstem volume (BM) and extra-cerebrospinal fluid volume (e-CSFV) were quantified by manual segmentation from two experts. The mean, SD, minimum, maximum, median, and 25th and 75th quartiles for intracranial structures volume were calculated per gestational week. A t test was used to compare our mean TBV values to previously reported values. The formulas to calculate intracranial structures volume derived from our data was created using a regression model. We also compared the predicted mean TBV values derived by our formula with the expected mean TBV predicted by the previously reported Jarvis' formula at each time point. Intraclass correlation coefficient (ICC) was calculated to convey association within and between observers for intracranial volumes. RESULTS. The intracranial volume data is presented as graphs and as tabular summaries. Means were compared with the expected TBV generated by the previously reported formula, showing statistically differences at 22, 26, 29, 30 weeks’ gestational age (GA) (all p < 0.05). Comparison between our data-derived formula and previously formula reported for TBV showed very similar values at every GA. Intra- and inter-observer agreement was high with no statistically significant differences between and within observers. CONCLUSION. We have shown that intracranial structures volume of fetal brain can be reliably quantified using 3-D volumetric MRI with a high degree of reproducibility and reinforces the existing data with more robust data in the earlier second and third stages of pregnancy.